Correction: Clinical correlation between serum cytokines and the susceptibility to Polygonum multiflorum-induced liver injury and an experimental study. Issue 24 (1st December 2022) - Zhang, Le; Niu, Ming; Wei, Ai-wu; Tang, Jin-fa; Li, Peng-yan; Song, Di; Bai, Zhao-fang; Liu, You-ping; Xiao, Xiao-he; Wang, Jia-bo
Abstract : Correction for 'Clinical correlation between serum cytokines and the susceptibility to Polygonum multiflorum -induced liver injury and an experimental study' by Le Zhang et al., Food Funct., 2022, 13, 825–833, ; https://doi.org/10.1039/D1FO03489H .